2015
DOI: 10.1063/1.4906929
|View full text |Cite
|
Sign up to set email alerts
|

Photothermally controlled Marangoni flow around a micro bubble

Abstract: We have experimentally investigated the control of Marangoni flow around a micro bubble using photothermal conversion. Using a focused laser spot acting as a highly localized heat source on Au nanoparticles/dielectric/Ag mirror thin film enables us to create a micro bubble and to control the temperature gradient around the bubble at a micrometer scale. When we irradiate the laser next to the bubble, a strong main flow towards the bubble and two symmetric rotation flows on either side of it develop. The shape o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
91
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 31 publications
3
91
0
Order By: Relevance
“…Quantification of the flow field and visualization of the convective structure of these instabilities has been the subject of several studies since the seminal work of Bénard [12] who observed a regular pattern of convective cells inside an evaporating thin liquid film with a free upper surface that was heated from the bottom. This observation, which was attributed to the density variation inside the liquid at that time but was thought to be the result of a surface tension gradient a few decades later [13,14], has hitherto been the inspiration behind several experimental [15,16], analytical [17,18] and numerical [19][20][21] studies.…”
Section: Introductionmentioning
confidence: 96%
“…Quantification of the flow field and visualization of the convective structure of these instabilities has been the subject of several studies since the seminal work of Bénard [12] who observed a regular pattern of convective cells inside an evaporating thin liquid film with a free upper surface that was heated from the bottom. This observation, which was attributed to the density variation inside the liquid at that time but was thought to be the result of a surface tension gradient a few decades later [13,14], has hitherto been the inspiration behind several experimental [15,16], analytical [17,18] and numerical [19][20][21] studies.…”
Section: Introductionmentioning
confidence: 96%
“…9 Recently, we demonstrated generation of rapid Marangoni vortex flows around a micro bubble using the thermoplasmonic effect of gold nanoparticles under laser illumination. 10 As a light absorbing layer, a thin film with two-dimensional gold nanoparticle array is prepared on the bottom surface of a narrow parallel plane channel. By focusing a laser onto the film, a micro bubble is created in the channel filled with water.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significance of Marangoni flow in practical engineering, the investigation of this subject is attracting an increasing amount of experts and scholars. The basic mechanism and the heat transfer process of Marangoni boundary layer flow have been extensively investigated in many literatures . The nanofluid of Marangoni convection on various occasions has been investigated .…”
Section: Introductionmentioning
confidence: 99%
“…The basic mechanism and the heat transfer process of Marangoni boundary layer flow have been extensively investigated in many literatures. [40][41][42] The nanofluid of Marangoni convection on various occasions has been investigated. [43][44][45] Lin and colleagues 46 and Ellahi and colleagues 47 presented research on particle shape effects on Marangoni convection boundary layer flow of a nanofluid.…”
Section: Introductionmentioning
confidence: 99%